The Analysis of the Effect of Online Learning Management During the Covid-19 Pandemic - Yunita Febriani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
The learning process during the pandemic is different from before where the implementation is carried out virtually or called online as the most appropriate way to break the chain of covid-19. Each agency or individual must be able to make the right management so that the learning process can be appropriate even though it is online. The study aims to find out how to manage education and learning online or at the student level when the pandemic was running. The study applied the literature study method. Through the literature study method, the author concludes that although online learning has a positive effect on educators and students in the learning process using appropriate learning management